Pengaruh Tingkat Partisipasi Perempuan Dalam Berwirausaha Terhadap Tingkat Sosial Ekonomi Keluarga Di Desa Umpungeng Kecamatan Lalabata Kabupaten Soppeng - esso, andi sawe ri; Sumriah, Sumriah; Nurdiana, Nurdiana; Hasan, Muhammad (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2019)
This study aims to determine the effect of the level of women's participation in entrepreneurship on the socio-economic level of the family. Technique of data analysis using simple linear regression analysis, sample determination with purposive random sampling and research data collection tools using a questionnaire. The results of this study indicate that: 1) The level of women's participation in entrepreneurship is positive and significantly affects the socio-economic level of the family; 2) The greater the level of women's participation in entrepreneurship, the higher the socio-economic level of the family